Lanthanum ferrite with hollow porous microsphere structure and preparation method and application thereof
The preparation of lanthanum ferrite (LaFeO3) with hollow porous microsphere structure by combining hydrothermal method and heat treatment solves the problems of cumbersome, time-consuming and cost-effectiveness of traditional preparation methods, improves the gas-sensitive performance and carrier transmission performance of the material, and provides great potential for it in gas-sensitive applications.
Patent Information
- Application Number
- CN202510035671.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-18
Smart Images

Figure CN119841356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas-sensitive materials, and in particular to a lanthanum ferrite with a hollow porous microsphere structure and a preparation method and application thereof. Background Art
[0002] A gas sensor is a device that converts information such as the composition and concentration of a gas into something that can be used by personnel, instruments, computers, etc., for detection and monitoring. Gas sensors detect target gases using methods such as temperature, current, and resistance. This technology has the advantages of good stability, repeatability, and high sensitivity, and is an ideal gas-sensitive material.
[0003] The quality of gas sensing performance mainly depends on the material's sensitivity to the target gas, response recovery time, selectivity, long-term stability, and detection limit. To improve the material's gas sensing performance, it is necessary to improve the material's sensitivity, reduce the response recovery time, structurally design and control the surface properties of the sensing material, and improve the material's gas sensing performance by synthesizing the surface morphology of the material. Lanthanum ferrite (LaFeO3) is a rare earth composite metal oxide with a perovskite structure. It is widely used in production due to its good redox properties and high conductivity at various temperatures. However, the current preparation methods of lanthanum ferrite (LaFeO3) materials mainly include traditional solid-phase synthesis and sol-gel methods. This method has the disadvantages of being cumbersome, time-consuming, and costly in the preparation of lanthanum ferrite (LaFeO3) materials. In addition, the prepared lanthanum ferrite (LaFeO3) has a low ability to accommodate cations and oxygen vacancies, and has poor carrier transport and redox properties.
[0004] Based on this, the present invention proposes a lanthanum ferrite with a hollow porous microsphere structure and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a lanthanum ferrite with a hollow porous microsphere structure and a preparation method and application thereof, so as to solve the problems that the traditional preparation method of lanthanum ferrite is complicated, time-consuming and costly, and the prepared lanthanum ferrite (LaFeO3) has a low ability to accommodate cations and oxygen vacancies, and has poor carrier transport and redox properties.
[0006] The technical solution of the present invention is achieved in this way:
[0007] The present invention provides a first solution: a method for preparing lanthanum ferrite having a hollow porous microsphere structure, wherein the method synthesizes lanthanum ferrite by combining a hydrothermal method with a heat treatment method, and specifically comprises:
[0008] Step 1: Mix 0.98 g of La(NO3)3 and 0.73 g of Fe(NO3)3 in 40 ml of deionized water at room temperature and fully dissolve them into a clear solution by magnetic stirring;
[0009] Step 2: Then, add citric acid monohydrate to the mixed solution and fully dissolve it into a clear solution by magnetic stirring;
[0010] Step 3: Then continue to add the surfactant, stir the mixed solution thoroughly, pour it into the reactor, and then place it in an oven and heat it at 180°C for 18 hours until it cools naturally to room temperature for use;
[0011] Step 4: Take out the solution and wash it by high-speed centrifugation, wash it with deionized water and anhydrous ethanol three times each, and then dry it in a vacuum oven at 60°C to obtain a brown powder;
[0012] Step 5: Grind the brown powder obtained after drying in a mortar and pour it into a corundum ark, then place the corundum ark in a tube furnace and heat it at 800°C for 5 hours in an air atmosphere to obtain lanthanum ferrite microspheres with a hollow porous structure.
[0013] In a preferred embodiment, the amounts of Fe(NO3)3 and Fe(NO3)3 in step 1 are both 3-6 mmol.
[0014] In a preferred embodiment, the amount of Fe(NO3)3 and Fe(NO3)3 in step 1 is 6 mmol.
[0015] In a preferred embodiment, the amount of citric acid monohydrate added in step 2 is 1.26-2.52 g.
[0016] In a preferred embodiment, the amount of citric acid monohydrate added in step 2 is 2.52 g.
[0017] In a preferred embodiment, the surfactant in step 3 is hexadecyltrimethylammonium bromide, and the amount of hexadecyltrimethylammonium bromide added is 1.09-4.37 g.
[0018] In a preferred embodiment, the amount of cetyltrimethylammonium bromide added is 4.37 g.
[0019] The present invention provides a second solution: a lanthanum ferrite with a hollow porous microsphere structure, characterized in that the chemical formula of the lanthanum ferrite is LaFeO3, the lanthanum ferrite is a microsphere structure with a porous surface and a hollow structure inside, and the size of the lanthanum ferrite microsphere is 1-2um.
[0020] In a preferred embodiment, the gas-sensitive response parameter of the lanthanum ferrite to 100 ppm ethanol gas is 6.8-9.1.
[0021] The present invention provides a third solution: application of lanthanum ferrite with a hollow porous microsphere structure in the preparation of an ethanol sensor.
[0022] Compared with the prior art, the present invention provides a lanthanum ferrite having a hollow porous microsphere structure and a preparation method and application thereof, which have the following beneficial effects:
[0023] 1. The present invention prepares lanthanum ferrite (LaFeO3) by combining a hydrothermal method with a heat treatment, which has the advantages of simple preparation process, low cost, and easy operation, and solves the problems of complicated, time-consuming and high cost in the preparation of traditional lanthanum ferrite (LaFeO3) materials.
[0024] 2. The present invention controls the synthesis reaction conditions through parameters, adds surfactants, and forms a thin film on the liquid surface to change the molecular arrangement of the liquid surface, so that the surface tension between liquids is significantly reduced, and porous hollow LaFeO3 microspheres are synthesized, which effectively improves the gas-sensing performance of the material.
[0025] 3. The lanthanum ferrite (LaFeO3) material prepared by the present invention has excellent optical and electrical properties, as well as good physicochemical properties and adjustable conductivity; at the same time, lanthanum ferrite (LaFeO3) is composed of multiple elements, and due to its easily adjustable structure and chemical properties, it can accommodate a large number of cations and oxygen vacancies, and has excellent carrier transport and redox properties, providing great potential for its application in gas sensing; it solves the problem that the lanthanum ferrite (LaFeO3) prepared by the traditional lanthanum ferrite preparation method has a low ability to accommodate cations and oxygen vacancies, and has poor carrier transport and redox properties.
[0026] 4. The porous structure of the lanthanum ferrite (LaFeO3) microspheres prepared by the present invention provides more channels for the diffusion of the tested gas and more active sites for the sensor reaction.
[0027] 5. Compared with other ethanol sensors on the market, the lanthanum ferrite (LaFeO3) prepared by the present invention has the advantages of short response recovery time, high sensitivity, low detection limit, good repeatability, and great potential as an ethanol sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained like these drawings without paying creative work.
[0029] Figure 1 Schematic diagram of SEM morphology, EDS and three element ratio characterization of LaFeO3 microspheres obtained in Example 1, Example 2 and Example 3 of the present invention;
[0030] Figure 2 Schematic diagram of TEM morphology, EDS mapping and three element ratio characterization of LaFeO3 microspheres obtained in Example 3 of the present invention;
[0031] Figure 3 Schematic diagram of XRD characterization of LaFeO3 microspheres obtained in Example 1, Example 2, and Example 3 of the present invention;
[0032] Figure 4 This is a schematic diagram of the response of the LaFeO3 microspheres obtained in Example 1, Example 2, and Example 3 of the present invention to 100 ppm ethanol gas at 290°C after being used as gas-sensitive materials.
[0033] Among them, Figure 1 In the figure, Figure (a) is a schematic diagram of the SEM morphology, EDS and three-element ratio characterization of the LaFeO3 microspheres obtained in Example 1; Figure (b) is a schematic diagram of the SEM morphology, EDS and three-element ratio characterization of the LaFeO3 microspheres obtained in Example 2; Figure (c) is a schematic diagram of the SEM morphology, EDS and three-element ratio characterization of the LaFeO3 microspheres obtained in Example 3;
[0034] exist Figure 2 In the figure, Figure (a) is the TEM morphology of LaFeO3 microspheres obtained in Example 3; Figure (b) is the EDS mapping of LaFeO3 microspheres obtained in Example 3; Figure (c) is a schematic diagram of the characterization of the proportions of three elements in LaFeO3 microspheres obtained in Example 3. DETAILED DESCRIPTION
[0035] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] The raw materials in the present invention are all purchased from commercial sources.
[0038] The room temperature in the present invention refers to 25±3°C.
[0039] Embodiment 1:
[0040] The following is attached to the instruction manual Figure 1-Figure 4 The preparation method of lanthanum ferrite (LaFeO3) with a hollow porous microsphere structure of the present invention is described. The method uses a combination of hydrothermal method and heat treatment to synthesize lanthanum ferrite (LaFeO3) material: first, lanthanum nitrate, ferric nitrate and citric acid monohydrate are mixed and dissolved in deionized water, fully stirred, and hexadecyltrimethylammonium bromide is added as a surfactant. Stirring continues until a uniform state, and a precursor is synthesized by a hydrothermal method; then, a lanthanum ferrite (LaFeO3) material with a hollow porous microsphere structure is obtained by a heat treatment process. Its specific preparation examples include:
[0041] Example 1:
[0042] Step 1: 0.98 g (3 mmol) of La(NO3)3 and 0.73 g (3 mmol) of Fe(NO3)3 were mixed and dissolved in 40 ml of deionized water at room temperature, and the mixture was fully dissolved into a clear solution by magnetic stirring;
[0043] Step 2: Then add 1.26 g of citric acid monohydrate to the mixed solution and fully dissolve it into a clear solution by magnetic stirring;
[0044] Step 3: Then continue to add 1.09g of hexadecyltrimethylammonium bromide (CTAB) as a surfactant, stir the mixed solution thoroughly, pour it into the 100ml reactor liner, put the liner into the reactor, and then place it in an oven at 180°C for 18 hours until it cools naturally to room temperature for use;
[0045] Step 4: Take out the solution and wash it by high-speed centrifugation, wash it with deionized water and anhydrous ethanol three times each, and then dry it in a vacuum oven at 60°C to obtain a brown powder;
[0046] Step 5: Finally, the brown powder obtained after drying is ground into a mortar and poured into a corundum ark, which is then placed in a tube furnace and heated at 800°C for 5 hours in an air atmosphere to obtain a brown powder, which is lanthanum ferrite (LaFeO3) microspheres with a hollow porous structure.
[0047] The prepared lanthanum ferrite (LaFeO3) material was used as a gas-sensitive material to make a gas sensor, and a gas-sensitive test was performed at an operating temperature of 290° C. The obtained gas-sensitive response to 100 ppm ethanol gas was 6.8.
[0048] Example 2:
[0049] Step 1: 0.98 g (6 mmol) of La(NO3)3 and 0.73 g (6 mmol) of Fe(NO3)3 were mixed and dissolved in 60 ml of deionized water at room temperature, and the mixture was fully dissolved into a clear solution by magnetic stirring;
[0050] Step 2: Then add 2.52 g of citric acid monohydrate to the mixed solution and fully dissolve it into a clear solution by magnetic stirring;
[0051] Step 3: Then continue to add 2.18g of hexadecyltrimethylammonium bromide (CTAB) as a surfactant, stir the mixed solution thoroughly, pour it into the 100ml reactor liner, put the liner into the reactor, and then place it in an oven at 180°C for 18 hours until it cools naturally to room temperature for use;
[0052] Step 4: Take out the solution and wash it by high-speed centrifugation, wash it with deionized water and anhydrous ethanol three times each, and then dry it in a vacuum oven at 60°C to obtain a brown powder;
[0053] Step 5: Finally, the brown powder obtained after drying is ground into a mortar and poured into a corundum ark, which is then placed in a tube furnace and heated at 800°C for 5 hours in an air atmosphere to obtain a brown powder, which is lanthanum ferrite (LaFeO3) microspheres with a hollow porous structure.
[0054] The prepared lanthanum ferrite (LaFeO3) material was used as a gas-sensitive material to make a gas sensor, and a gas-sensitive test was performed at an operating temperature of 290° C. The obtained gas-sensitive response to 100 ppm ethanol gas was 7.8.
[0055] Example 3:
[0056] Step 1: 0.98 g (6 mmol) of La(NO3)3 and 0.73 g (6 mmol) of Fe(NO3)3 were mixed and dissolved in 60 ml of deionized water at room temperature, and the mixture was fully dissolved into a clear solution by magnetic stirring;
[0057] Step 2: Add 2.52 g of citric acid monohydrate to the mixed solution and fully dissolve it into a clear solution by magnetic stirring;
[0058] Step 3: Then continue to add 4.37g of hexadecyltrimethylammonium bromide (CTAB) as a surfactant, stir the mixed solution thoroughly, pour it into the 100ml reactor liner, put the liner into the reactor, and then place it in an oven at 180°C for 18 hours until it cools naturally to room temperature for use;
[0059] Step 4: Take out the solution and wash it by high-speed centrifugation, wash it with deionized water and anhydrous ethanol three times each, and then dry it in a vacuum oven at 60°C to obtain a brown powder;
[0060] Step 5: Finally, the brown powder obtained after drying is ground into a mortar and poured into a corundum ark, which is then placed in a tube furnace and heated at 800°C for 5 hours in an air atmosphere to obtain a brown powder, which is lanthanum ferrite (LaFeO3) microspheres with a hollow porous structure.
[0061] The prepared lanthanum ferrite (LaFeO3) material was used as a gas sensitive material to make a gas sensor, and a gas sensitive test was performed at an operating temperature of 290° C. The obtained gas sensitive response to 100 ppm ethanol gas was 9.1.
[0062] The lanthanum ferrite (LaFeO3) materials prepared by the methods described in Examples 1 to 3 were observed and studied, and the SEM morphology, EDS mapping and three-element ratio characterization schematic diagrams of the LaFeO3 microspheres obtained in Examples 1, 2 and 3 are shown in Table 1; the TEM morphology, EDS mapping and three-element ratio characterization schematic diagrams of the LaFeO3 microspheres obtained in Example 3 are shown in Table 2; the XRD characterization schematic diagram of the LaFeO3 microspheres obtained in Examples 1, 2 and 3 is shown in Table 3; the LaFeO3 microspheres obtained in Examples 1, 2 and 3 are used as gas-sensitive materials, and the response to 100 ppm ethanol gas at 290°C is shown in Figure 2. Figure 4 As shown; through the above Figure 1-Figure 4 It can be seen that the lanthanum ferrite microspheres of the lanthanum ferrite (LaFeO3) material prepared by the method described in Examples 1 to 3 above are about 1-2 um in size, porous on the surface, and hollow inside; after inspection, it is shown that the material has excellent optical and electrical properties, good physicochemical properties and adjustable conductivity, is composed of multiple elements, and has easily adjustable structures and chemical properties, so that it can accommodate a large number of cations and oxygen vacancies, and has excellent carrier transport and redox properties, which provides great potential for its application in gas sensing;
[0063] Among them, the porous structure can provide more channels for the diffusion of the tested gas and more active sites for the sensor reaction.
[0064] Embodiment 2:
[0065] Different from the above-mentioned Example 1, the lanthanum ferrite (LaFeO3) material prepared by the method described in Example 1 and the existing NiO material and α-MnO2 material are used to prepare a gas sensor, and the gas-sensitive response of ethanol is tested, and the detection results are shown in Table 1 below;
[0066] Figure 1 : Performance comparison table
[0067]
[0068] Among them: In Table 1, reference documents: [1] C. Su, L. Zhang, Y. Han et al., "Controllable synthesis of crescent-shaped porous NiO nanoplates for conductometric ethanol gas sensors," Sensors and Actuators B-Chemical, vol. 296, 126642, 2019.
[0069] [2] Liu C, Navale ST, Yang ZB, et al. Ethanol gas sensingproperties ofhydrothermally grownα-MnO2 nanorods. Journal of Alloys and Compounds, 727 (2017) 362-369.
[0070] From Table 1, it can be seen that the lanthanum ferrite (LaFeO3) material prepared by the method described in Example 1 has a high response to ethanol, reaching 9.1, and at a relatively low concentration, compared with ethanol sensors prepared from other materials, it has a very outstanding advantage in having a higher response, and the lanthanum ferrite (LaFeO3) sensor has a short response recovery time, high sensitivity, a low detection limit, and good repeatability. There is great potential for using lanthanum ferrite (LaFeO3) as an ethanol sensor.
[0071] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0072] The above-described embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing lanthanum ferrite having a hollow porous microsphere structure, characterized in that: The method uses a hydrothermal method combined with a heat treatment method to synthesize lanthanum ferrite, specifically comprising: Step 1: Mix 0.98 g of La(NO3)3 and 0.73 g of Fe(NO3)3 in 40 ml of deionized water at room temperature and fully dissolve them into a clear solution by magnetic stirring; Step 2: Then, add citric acid monohydrate to the mixed solution and fully dissolve it into a clear solution by magnetic stirring; Step 3: Then continue to add the surfactant, stir the mixed solution thoroughly, pour it into the reactor, and then place it in an oven and heat it at 180°C for 18 hours until it cools naturally to room temperature for use; Step 4: Take out the solution and wash it by high-speed centrifugation, wash it with deionized water and anhydrous ethanol three times each, and then dry it in a vacuum oven at 60°C to obtain a brown powder; Step 5: Grind the brown powder obtained after drying in a mortar and pour it into a corundum ark, then place the corundum ark in a tube furnace and heat it at 800°C for 5 hours in an air atmosphere to obtain lanthanum ferrite microspheres with a hollow porous structure.
2. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 1, characterized in that: The amounts of Fe(NO3)3 and Fe(NO3)3 in step 1 are both 3-6 mmol.
3. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 2, characterized in that: The amount of Fe(NO3)3 and Fe(NO3)3 in step 1 is 6 mmol.
4. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 1, characterized in that: The amount of citric acid monohydrate added in step 2 is 1.26-2.52 g.
5. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 4, characterized in that: The amount of citric acid monohydrate added in step 2 is 2.52 g.
6. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 1, characterized in that: The surfactant in step 3 is hexadecyltrimethylammonium bromide, and the amount of hexadecyltrimethylammonium bromide added is 1.09-4.37g.
7. The method for preparing lanthanum ferrite having a hollow porous microsphere structure according to claim 6, characterized in that: The added amount of the hexadecyltrimethylammonium bromide is 4.37 g.
8. A lanthanum ferrite having a hollow porous microsphere structure prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The chemical formula of the lanthanum ferrite is LaFeO3. The lanthanum ferrite is a microsphere structure with a porous surface and a hollow structure inside, and the size of the lanthanum ferrite microsphere is 1-2um.
9. The lanthanum ferrite having a hollow porous microsphere structure according to claim 8, characterized in that: The gas-sensitive response parameter of the lanthanum ferrite to 100 ppm ethanol gas is 6.8-9.
1.
10. Application of lanthanum ferrite with hollow porous microsphere structure in the preparation of ethanol sensor.
Citation Information
Cited By
Preparation method of lanthanum ferrite / biochar composite material and application of lanthanum ferrite / biochar composite material in gas detection
CN120420951A
A method for preparing a lanthanum ferrite / biochar composite material and its application in gas detection.
CN120420951B